Pengaruh Strategi Quantum Learning Terhadap Prestasi Belajar Pendidikan Agama Islam di SMAN 3 Takengon - Chairina Inayah; Muhammad Rijali Rais; Nurul Aini (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to analyze the effect of the Quantum Learning strategy on the learning achievement of Islamic Religious Education students at SMAN 3 Takengon. The study used a quantitative approach with a True Experimental Design and a Pre-test Posttest Control Group Design. The study population was 51 students with a sample of 27 students selected using the Simple Random Sampling technique. The research data were obtained through learning achievement tests before and after treatment, then analyzed using the unpaired two-sample mean difference test. The results showed that the implementation of the Quantum Learning strategy had a significant effect on student learning achievement. This was evidenced by a significance value (2-tailed) of 0.009 < 0.05, which indicated a difference in learning outcomes between the experimental class and the control class. The research findings indicated that the Quantum Learning strategy was able to create a more active, enjoyable learning atmosphere and increase student involvement in Islamic Religious Education learning. The contribution of this study lies in strengthening empirical evidence regarding the effectiveness of the Quantum Learning strategy in improving learning achievement of Islamic Religious Education at the secondary school level, especially in a learning context that is still dominated by conventional methods